Expression of CYP2E1 and CYP2U1 Proteins in Amygdala and Prefrontal Cortex: Influence of Alcoholism and Smoking. (May 2015) - Toselli, Francesca; Booth Depaz, Iris M.; Worrall, Simon; Etheridge, Naomi; Dodd, Peter R.; Wilce, Peter A.; Gillam, Elizabeth M. J.
<x xml:space="preserve">Abstract</x> Background The tissue‐specific expression of cytochrome P450 enzymes (CYP, P450) in the human brain may influence the therapeutic response to, and side effects of, neuroactive drugs including alcohol. However, the distribution of many P450s, especially poorly characterized CYP2 forms, within specific regions of the brain remains obscure, partly due to the paucity of available tissue and difficulty in discriminating between related P450s with available antibodies. Methods In this study, we analyzed the expression of CYP2A6, CYP2B6, CYP2D6, CYP2E1, CYP2J2, CYP2S1, CYP2U1, and CYP2W1 proteins in human prefrontal cortex (PFC) and amygdala (AMG) by immunoblotting with antibodies for which the P450 form specificity had been enhanced by affinity purification. These brain regions were selected as they mediate the addictive effects of cigarette smoking and alcohol consumption, substances known to modulate P450 expression in other tissues. PFC and AMG samples from alcoholic smokers, alcoholic nonsmokers, nonalcoholic smokers, and nonalcoholic nonsmokers were studied to assess the effect of alcohol use and smoking on the expression of these proteins. Results Of the P450s studied, CYP2E1 and CYP2U1 were expressed in all samples analyzed (n = 26 and 22 for CYP2E1 and CYP2U1, respectively), and elevated in alcoholics. CYP2U1 expression was also slightly increased in smokers. Expression of both P450s was increased in AMG compared to PFC of the same individuals. Conclusions This is the first report of CYP2E1 and CYP2U1 protein expression in human AMG. Our results suggest that CYP2U1 expression may be modulated by alcohol and tobacco, with potential consequent effects on the metabolism of drugs and endogenous chemicals by this enzyme.